Corporate Governance through the EVA Tool: A Good Corporate Performance Driver - Prusty, Twinkle (Journal of Asian Business Strategy, 2013)
The appraisal of the effect of Corporate Governance (CG) to the performance of the firm measured by Economic Value Added (EVA), is the essence of the study from the gaining importance of motivating managers’ i.e. enabling good governance for getting rid of destructive activities and investing in those projects that are expected to enhance shareholder value. The implications of the practices of corporate governance on the economic value added, of the sample companies are being explored and assessed to find out whether its conformance will improve corporate performance enthused by valuation reporting, EVA, which is important for investment decision making and consistent internal governance. It necessitates establishing whether the components of corporate governance viz., equitable treatment of shareholders, transparency and disclosure influences the economic value added, an superior performance metric, by raising the consciousness of their relationship thereby, without relying on the bland accounting results flaunted by the corporate.